Review of Big Data Integration in Construction Industry Digitalization - Yousif, Omar Sedeeq; Zakaria, Rozana Binti; Aminudin, Eeydzah; Yahya, Khairulzan; Mohd Sam, Abdul Rahman; Singaram, Loganathan; Munikanan, Vikneswaran; Yahya, Muhamad Azani; Wahi, Noraziah; Shamsuddin, Siti Mazzuana (Frontiers in Built Environment, 2021)
The 2030 agenda for sustainable development has embraced the importance of sustainable practices in the construction industry. In parallel with the revolution of industry 4.0, the advancement of technology offering advanced data management which the construction practices have been revolutionized by the capability to process and extract value from data. This phenomenon attracts the requirement of Big Data (BD). The construction industry deals with large volumes of heterogeneous data; which is expected to increase exponentially following an intense use of modern technologies. This research presents a comprehensive study of the literature, investigating the potential application of BD integration in the construction industry. The adoption of such technologies in this industry remains at a nascent stage and lags broad uptake of these technologies in other fields. The Construction Industry is driving to boost its productivity through the implementation of data technologies; hence, significant research is needed in this area. Currently, there is a lack of deep comprehensive research on BD integration applications that provide insight for the construction industry. This research closes the gap and gives an overview of the literature. The discussion presented the current utilization, the issues, and ways for potential works along with the challenges companion with the implementation.